Infecciones respiratorias y su incidencia en el enfisema pulmonar con adultos entre 40 y 60 años que asisten al Hospital Martín Icaza del Cantón Babahoyo durante octubre 2018 a abril 2019 - Chica Tomalá, Jaela Hortencia (2019)
The present investigative work originates in the Martin Icaza Hospital of the City of Babahoyo, province of Los Ríos, lies in the appearance of respiratory infections and its incidence in patients with pulmonary emphysema between 40 and 60 years attending consultation in the area of observation. The main objective of this work is to: Determine the influence of respiratory infections with techniques and procedures for the purpose of preventing pulmonary emphysema in adult patients between 40 and 60 years of the Martín Icaza Hospital of Babahoyo Canton. This with the intention of preserving the life of patients with pulmonary emphysema. In the methodology used for this research, the types of research were taken; bibliographic - Documentary and descriptive. In addition to the investigative, deductive and inductive methods, the target population is 25 adult between 40 and 60 years old with pulmonary emphysema. From the survey carried out at the Martín Icaza Hospital, it was found that more than 60% of respondents assumed to have contracted pulmonary emphysema due to being active smokers and 95% stated that they would like to receive more information regarding prevention, causes and treatment of respiratory infections and thus avoid contracting them, since they assume a risk for said patients. It is concluded that the main cause of this disease is the consumption of tobacco or wood smoke.